Asymmetrical hybrid‐controlled half‐bridge LCC resonant converter with low conduction loss and wide ZVS operation range. Issue 21 (1st October 2017) - Lin, Leiming; Xu, Jianping; Chen, Yiming; Wang, Xiaoqiang; Cao, Jing
Abstract : An asymmetrical hybrid‐controlled half‐bridge LCC resonant converter which integrated a buck–boost converter and a half‐bridge LCC resonant converter is proposed. It benefits with wide soft switching range, low conduction loss and high power density. By utilising an asymmetrical hybrid control strategy, its switching frequency and duty ratio can be adjusted simultaneously. The proposed LCC resonant converter maintains output voltage regulation and zero‐voltage switching of switches in wide input voltage and load variation range. Experiment results of a 500 W prototype are provided to verify the theoretical analysis results.